2016
DOI: 10.5539/jedp.v6n2p183
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress and Psychiatric Symptoms in Swedish Upper Secondary School Students

Abstract: Background: Previous studies in adolescents have rarely used validated questionnaires to assess stress and psychiatric symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 49 publications
6
19
0
Order By: Relevance
“…The female adolescents in both countries in our study reported lower scores on the sub-scale 'Psychological well-being' than the male adolescents. A lower psychological well-being in females than males is well-known from earlier findings in Sweden (Bremberg, 2006;Folkhälsomyndigheten, 2010;Hagquist & Forsberg, 2007;Petersen, 2007;Thorsén, Antonson, Sundquist, & Sundquist, 2016), although, to our best knowledge, it has never previously been shown in the Soviet-bloc. The lower self-esteem in females in the sub-scale 'psychological well-being' in both Sweden and Bulgaria could possibly have a biological explanation, as we see no difference between the two countries.…”
Section: Psychological Well-beingsupporting
confidence: 67%
“…The female adolescents in both countries in our study reported lower scores on the sub-scale 'Psychological well-being' than the male adolescents. A lower psychological well-being in females than males is well-known from earlier findings in Sweden (Bremberg, 2006;Folkhälsomyndigheten, 2010;Hagquist & Forsberg, 2007;Petersen, 2007;Thorsén, Antonson, Sundquist, & Sundquist, 2016), although, to our best knowledge, it has never previously been shown in the Soviet-bloc. The lower self-esteem in females in the sub-scale 'psychological well-being' in both Sweden and Bulgaria could possibly have a biological explanation, as we see no difference between the two countries.…”
Section: Psychological Well-beingsupporting
confidence: 67%
“…The girls in both countries had lower results in the sub-scale 'Psychological well-being' than the boys at both waves. Thus the pattern with girls reporting lower levels of psychological wellbeing that we are used to seeing in western democracies over decades [9,11,26] was also found in Bulgaria at both times, with different governance.…”
Section: Main Findingssupporting
confidence: 52%
“…The deterioration of 'Psychological well-being' in Sweden follows other studies in Western democracies over in the whole post-war period [26,[41][42][43]. Many hypotheses concerning the genesis of this have been formed.…”
Section: The Deterioration Of Psychological Well-being In Swedenmentioning
confidence: 53%
See 1 more Smart Citation
“…Good sleep is important for mental as well as somatic health in adolescents (1)(2)(3)(4)(5)(6). In Sweden, studies have shown that people aged 16 to 24 years, especially females, have over time exhibited an increase in symptoms of anxiety, depression, and somatization (7,8). Psychiatric disorders have, according to the World Health Organization (WHO), now become the second most common non-communicable health concern worldwide (cardiovascular disease being the leading concern) (9, 10).…”
Section: Introductionmentioning
confidence: 99%